Hydrodynamic investigation of bubble-column reactors: effect of column configuration - Akhtar, Abid; Tade, Moses; Pareek, Vishnu (John Wiley & Sons, Ltd, 2010)
Bubble-column reactors are quite popular in the chemical, biochemical and petrochemical industries due to their relatively simple construction, favourable heat and mass transfer properties and low operating cost. Among the various design parameters, column geometry (configuration) has a significant impact on the overall throughput. In this study, an experimental investigation of the bubble-column configuration on its hydrodynamics has been conducted with three different sizes of the column (ID = 10–45 cm). A comparison in terms of the overall gas holdup as well as localised bubble properties is performed using the four-point optical technique and hydrodynamic similarities/dissimilarities are discussed. The study showed that the overall gas holdup was a function of the gas flow rate. For the range of gas velocity investigated (9.5–22.3 cm3/ min), the smaller column had 50–60% more holdup than the bigger column. Localised bubble properties exhibited similar behaviour (i.e. higher values for the smaller column). A comparative study of L/D illustrated an invariant behaviour at a high value of L/D (>5.5). A low L/D (≤1.5), however, showed a prominent influence on hydrodynamics.